Methods of the policy process - Weible, Christopher M.; Workman, Samuel (Routledge, Taylor & Francis Group, 2022)
The design of policy process research / Samuel Workman & Christopher M. Weible -- How to conduct a multiple streams study / Reimut Zohlnhöfer, Nicole Herweg, Nikolaos Zahariadis -- The code and craft of punctuated equilibrium / Samuel Workman, Frank R. Baumgartner and Bryan D. Jones -- Methods for applying policy feedback theory / Sorelle, Mallory and Jamila Michener -- Advocacy coalition framework : advice on applications and methods / Adam Douglas Henry, Karin Ingold, Christopher M. Weible, & Daniel Nohrstedt -- Conducting narrative policy framework research : from theory to methods / Michael D. Jones, Mark K. McBeth, Elizabeth A. Shanahan, Aaron Smith-Walter, and Geoboo Song -- Innovation and diffusion : connecting theory and method / Andrew Karch -- Methods for analyzing social dilemmas and institutional arrangements within the institutional analysis and development framework / Edella Schlager, Saba Siddiki and Michael Cox -- Methodological approaches to the ecology of games framework / Mark Lubell, Matthew Hamilton, Jack Mewhirter, Francesca Vantaggiato, and Ramiro Berardo -- The evaluation and advancement of policy process research / Christopher M. Weible & Samuel Workman.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Forschungsmethode; Staatstätigkeit; Politikfeldanalyse; Politischer Prozess